Fundamental study on the effects of epha2 inhibitation in angiogenesis signaling pathways of human malignant glioma cells - Farizan, Ahmad (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2018)
An oncreasing number of studies have shown a correlation between EphA2 overexpress1on and hogh actovnoes of angiogenesos in malignant gliomas To test v.'hether EphA2 regulates angiogenesis via VEGF and it's receptors, VEGFR-1 and VEGFR-2. the genes and proteon expression levels were evaluated following gene knockdown with so RNA. Prolrferai!On a&say showed reduction of relative cell VIability from 24 hour to 48 hour upon siRNA transfectoon (p=0.02). EphA2 knocl.down signlfocanlly suppressed the expression of VEGF (p:O 023) and VEGFR-2 (o:0.0299) at gene levels in U-87 cell ~ne Contrary the similar knockdown effects 1iii'3S not seen in DBTRG cell hne. Gene expression analysos in DBTRG showed a trend of elevated VEGF and downregulaled VEGFR-2 With no significant difference. VEGFR- 1 gene expression was not detected on both cell lines. At prote•n level. EphA2 expressoon before and after siRNA ttansfection was nol detected 1n bolh CEll lines. The differences seen In genes regulation of U-87 and DBTRG cell lines may be due to the fact that both cell hnes are from different orogon. Our results suggested possobte role of EphA2 In angiogenesos pathway via VEGF and VEGFR-2 regulations on U-87 cells Act1vation of VEGFNEGFR-2 complex may tngger mu1t1ple downstream s1gnallng pathways which resulting on endothelial cell survival, prohferat1on, migration. and dillerentiatKln as well as vascular permeabnity.